IMPLEMENTATION OF THE PEDAGOGICAL CONTENT KNOWLEDGE (PCK) LEARNING APPROACH IN NATURAL SCIENCE LESSONS ON STUDENT LEARNING INTERESTS - Mella Mutika Sari; Ellyna Hafizah; Annisa Rahmalia (Sean Institute, 2023)
This study examines how implementing the Pedagogical Content Knowledge (PCK) learning approach in science lessons affects students’ learning interests. The research was conducted in December. The population of class VIII students of SMP GIBS was 20 people. This type of research was a quantitative study using a method of two classes: class VIII Boys and class VIII Girls. Students sampled in this study filled out 20 statements in a questionnaire the teacher gave. The sample used was VIII Girls class students. As many as 16 students were present at the meeting. Students who filled out the previous questionnaire had studied as many as three sessions at the last meeting, with the topic Introduction to Force, Newton’s Laws, and Work. After the previous meeting, the teacher gave the students a questionnaire. The questionnaire is a tool to measure students’ interest in learning. The results showed that overall 71.75% of students were interested in the teaching given by the science teacher. This means that it can be concluded that most of the students in class VIII Girls SMP Global Islamic Boarding School feel happy with the implementation of Pedagogical Content Knowledge (PCK) in style.